Konsep Epistemologi Mulla Shadra - Happy Saputra (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2016)
The study of epistemology is considered critical in the discourses of Islamic theology. One of the Islamic scholars who had a comprehensive concept of epistemology was Mulla Shadra. His concept was influenced by four post Mongolia, classical-Islamic philosophy; masysya'i (Peripatetic), Ishraqi (Illmunianionis), 'Irfani (Gnosis, Sufism or Sufism), and kalam (Islamic theology). The four schools of thought converged into each other equipping him with a basis to establish a grand synthesis. The philosophy of Mulla Shadra, better known and more popular as al-hikmah al-muta'aliyah, is a kind of wisdom or philosophy based on the pure metaphysics foundation acquired through intellectual intuition and logical formulation by using rational arguments. Hi divided the philosophy into two categories. The first is the theoretical concept which refers to the understanding of everything as they are. Its realization is reflected in a rational world, including soul as stated by al-Farabi and Ibn Sina. The second is the practical concept which refers to the achievement of the achievement suitable for the soul.